Les rapports entre les genres dans l’alpinisme français et anglais - Delphine Moraldo (Revue de Géographie Alpine)
From its emergence in the middle of the 19th century, mountaineering has always been a very masculine activity, which is practised by men and which conveys manly representations. The study of the very few autobiographies written by female mountaineers tells us something about gender relations in French and British mountaineering. First of all, the scarcity of these narratives (compared to narratives written by men) is evidence of the symbolical place of women in mountaineering. Then, theses texts bring to light the atypical trajectories and social dispositions (each time replaced within the social and historical context of the life of the author) of these women. Finally, they show how female mountaineers consider male mountaineers of their time – men are omnipresent in female narratives, whereas women are almost absent in men’s ones – and reveal implicitly their inferior status. In this study, historical and social context, although not central, is important: each time, it is in relation to the social and sport norms of a time period that one can appraise the place of female mountaineers.